2016
DOI: 10.1038/nsmb.3243
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor ERG recruits CCR4–NOT to control mRNA decay and mitotic progression

Abstract: nature structural & molecular biology advance online publication a r t i c l e sAlthough undisputable evidence has clearly demonstrated that the nuclear steps of mRNA processing are mechanistically linked to transcription, a conceptual evolution in gene regulation has come with the realization that transcription might also be functionally connected to more remote processes occurring in the cytoplasm, such as mRNA decay 1,2 . Cytoplasmic mRNA decay is initiated by deadenylation, a rate-limiting event during whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…CNOT2 encodes a subunit of the multi-component CCR4-NOT complex, involved in gene expression regulating mRNA synthesis, degradation, splicing, transport, and localization (Jeong, Kwon, Jeong, Sohn, & Kim, 2017;Rambout et al, 2016). According to its wide biological functions, it is ubiquitously expressed (https://www.genecards.org),…”
Section: Resultsmentioning
confidence: 99%
“…CNOT2 encodes a subunit of the multi-component CCR4-NOT complex, involved in gene expression regulating mRNA synthesis, degradation, splicing, transport, and localization (Jeong, Kwon, Jeong, Sohn, & Kim, 2017;Rambout et al, 2016). According to its wide biological functions, it is ubiquitously expressed (https://www.genecards.org),…”
Section: Resultsmentioning
confidence: 99%
“…Indirect effects of CNOT-mediated transcriptional repression could involve the association or regulation of transcription factors. Examples for such a mechanism are interactions of CNOT1 with estrogen receptor α, CNOT9 binding to c-Myb 20 and CNOT2 interaction with ERG 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a new transcription-independent role of PER cannot be excluded, different mechanisms have been revealed that link transcription with the control of mRNA polyadenylation and stability (48,49). Notably, interactions between the transcription machinery and the CCR4-NOT complex indicate that mRNA deadenylation can be regulated at the transcriptional level (50)(51)(52)(53), raising the possibility that PER might interfere with POP2 activity through its role as a transcriptional repressor. For example, CBP/p300 acetylates CAF1 to promote its activity (52).…”
Section: Discussionmentioning
confidence: 99%